INTERNATIONAL RESPONSIBILITY OF THE ISRAELI AGGRESSION ON GAZA STRIP IN 2014 - Elshobake, Mohammed R M (PEOPLE: International Journal of Social Sciences, 2019)
On 8th July 2014, the Israeli occupation commenced a military operation against the Gaza Strip. This offensive lasted 50 days, between 8th July to 28th August 2014. During this period, the Israeli military committed many international crimes, which killed thousands of Palestinian civilians, destroyed thousands of civilian objects, and caused a humanitarian crisis in the Gaza Strip. This paper will discuss the effects of the Israeli operation on the Gaza Strip. This paper also seeks to detail the crimes committed by Israeli military during its aggression upon the Gaza Strip in 2014. We examine the international responsibility of the Israeli Aggression in the context of international law, and mainly used analytical and library research to realize this. The rules of international law in general, and international humanitarian law in particular, were utilized in this study to elucidate the legal descriptions. It was confirmed that the Israeli occupation committed war crimes, crimes against humanity, and genocide during the course of their aggression. There are problems in the International Criminal Court (ICC) proceedings, which may prevent the Israeli military from facing a trial. We intend to provide alternative to trials, due to the perceived ineffectiveness of the ICC.